2019
DOI: 10.1038/s41394-019-0227-3
|View full text |Cite
|
Sign up to set email alerts
|

Using cannabis for pain management after spinal cord injury: a qualitative study

Abstract: Study design A descriptive qualitative study. Objectives To explore why individuals with spinal cord injury (SCI) choose to use cannabis to manage their pain and their experiences in doing so. Setting Community-dwelling adults with SCI in New Zealand. Methods Semi-structured interviews were conducted with individuals who had a SCI, experienced pain, and self-reported use of cannabis to manage their pain. Interviews were recorded, transcribed, and subject to thematic analysis. Results Eight individuals particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…including three interview-based studies also reported that cannabis was preferred over prescribed medications due to fewer side effects, including less dehydration, memory loss and drowsiness [ 46 , 50 , 54 , 72 ]. Overall, cannabinoids were subjectively rated as the most effective pain relief treatment across several studies [ 44 , 46 , 50 , 53 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…including three interview-based studies also reported that cannabis was preferred over prescribed medications due to fewer side effects, including less dehydration, memory loss and drowsiness [ 46 , 50 , 54 , 72 ]. Overall, cannabinoids were subjectively rated as the most effective pain relief treatment across several studies [ 44 , 46 , 50 , 53 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, two studies [ 55 , 58 ], comprised of five therapeutic intervention arms, reported the impact of cannabinoids on functional independence measures (Barthel Activities of Daily Living Index, Rivermead Mobility Index, General Health Questionnaire 28, Functional Independence Measure) and found that cannabinoids had no statistically significant effect (Table 6 , Table e-6 ) [ 55 , 58 ]. On the contrary, one interview-based study reported that the analgesic properties of cannabis use could improve the quality of life due to functional improvement [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…The use of cannabis for SCI individuals has been trialled in New Zealand. [11] Patients described prescribed medications such as opiates and neuroleptic based medications to have side-effects leaving them in a 'zombie-like state' such as drowsiness, frustration, and exhaustion. Participants reported cannabis reduced their pain quickly and allowed them to engage in daily living activities without the drowsiness of traditional prescribed pain medications.…”
Section: Discussionmentioning
confidence: 99%
“…Cannabinoids are involved in a variety of physiological functions including metabolism [ 37 ], behavior [ 38 ], emotion, pain [ 39 ], motor coordination [ 40 ], and insulin sensitivity [ 41 ]. However, the effects of chronic marijuana use on human pancreatic tissue and islets have not been investigated.…”
Section: Discussionmentioning
confidence: 99%